Effects of Melatonin on Nervous System Aging: Neurogenesis and Neurodegeneration - Golmaryam Sarlak; Anorut Jenwitheesuk; Banthit Chetsawang; Piyarat Govitrapong (Elsevier, 2013)
Neural aging as a progressive loss of function involves central and peripheral postmitotic neurons and neural stem cells (NSCs). It promotes neurodegeneration, impairs neurogenesis, and can be considered a cause of cognitive impairment and sensory and motor deficits in the elderly. Age-related morphological atrophic changes and cellular alterations are addressed by neural aging mechanisms. Neurogenesis declines during aging through several mechanisms such as an increase in quiescence state, changes in lineage fate, telomerase dysfunction, the failure of the DNA repair system, increased apoptosis, and the impairment of self-renewal. The self-renewal transcriptional factor Sox2 has been correlated with retrotransposon L1 and certain cell-cycle-and epigenetic-related factors, which are sometimes considered age-related factors in NSC aging. As neurogenesis decreases, non-mitotic neurons undergo neurodegeneration by oxidative stress, sirtuin, insulin signaling and mTOR alteration, mitochondrial dysfunction, and protein misfolding and aggregation. As neurodegeneration and impaired neurogenesis promote the nervous system aging process, the identification of neuronal anti-aging is required to raise life expectancy. The role of melatonin in increasing neurogenesis and protecting against neurodegeneration has been investigated. Here, we review nervous system aging that is correlated with mechanisms of neurodegeneration and the impairment of neurogenesis and evaluate the effects of melatonin on these processes. Keywords:: aging, neurogenesis, neurodegeneration, melatonin, nervous system